Associação entre qualidade de vida relacionada à saúde e situação alimentar em adolescentes - Molon, Luara (2020)
Food insecurity (FI) refers to the situation in individuals - although having access to the food needed to meet their energy needs - are uncertain as to the stability of such state, and may be forced to reduce the quality/quantity of necessary food for survival. Considering the possible consequences for health, quality of life, and subjective well-being, the present study investigated associations between FI and health-related quality of life (HRQoL) in adolescents, according to their own perceptions. A quantitative cross-sectional study was conducted in a municipality in the 8th Paraná southwestern health division. Sample was comprised by 256 male and female adolescents aged between 12 and 17 years (mean= 13.8, SD = 1.49). The Brazilian Food Insecurity Scale (EBIA) was used to assess food security (α=0.78) and the Kidscreen 52 was used for HRQoL assessment (α=0.96). Correlation analyses, hierarchical linear regression models and mean comparisons were conducted in the Statistical Package for the Social Sciences (SPSS, version 23). According to the results, 58.6% of the sample classified themselves as having a situation of food security, and 41.4% reported food insecurity. Severe FI was not found in the sample. Food insecurity showed significant correlation with the number of residents per household, mother's education, and family income. Regression models indicated that family income, total residents in the household, and the Kidscreen 52 domain of financial aspects predicted FI. An increase in food insecurity was correlated with decreased HRQoL in all its domains, with adolescents with FI presenting significantly lower HRQoL than adolescents in food security (FS) in seven out of ten HRQoL domains. Hence, the study suggested that social and financial aspects were factors associated with food insecurity as assessed from the adolescents’ perspective.